Inter- and intraspecific phenotypic plasticity of three phytoplankton species in response to ocean acidification. (28th February 2017) - Hattich, Giannina S. I.; Listmann, Luisa; Raab, Julia; Ozod-Seradj, Dorthe; Reusch, Thorsten B. H.; Matthiessen, Birte
Abstract : Phenotypic plasticity describes the phenotypic adjustment of the same genotype to different environmental conditions and is best described by a reaction norm. We focus on the effect of ocean acidification on inter- and intraspecific reaction norms of three globally important phytoplankton species ( Emiliania huxleyi, Gephyrocapsa oceanica and Chaetoceros affinis ). Despite significant differences in growth rates between the species, they all showed a high potential for phenotypic buffering (similar growth rates between ambient and high CO2 conditions). Only three coccolithophore genotypes showed a reduced growth in high CO2 . Diverging responses to high CO2 of single coccolithophore genotypes compared with the respective mean species responses, however, raise the question of whether an extrapolation to the population level is possible from single-genotype experiments. We therefore compared the mean response of all tested genotypes with a total species response comprising the same genotypes, which was not significantly different in the coccolithophores. Assessing species reaction norms to different environmental conditions on short time scale in a genotype-mix could thus reduce sampling effort while increasing predictive power.